Perancangan Platform E-Commerce untuk Peningkatan Penjualan Produk Kerajinan Tangan Menggunakan OpenCart pada UMKM Kec. Lubuk Tarok - Amanda Putri, Diva; Annas, Firdaus; Yunita, Ermai (JOVISHE : Journal of Visionary Sharia Economy, 2024)
In today's digital era, the development of technology and communication has brought significant changes in various aspects of life, and also includes the business world. One form of innovation that has emerged is e-commerce, which allows businesses to promote their products online. In Lubuk Tarok sub-district, there are still many Micro, small and medium enterprises (MSMEs) that have produced a handicraft made of mahogany wood, but still face challenges in increasing the sales of their products. Therefore, this research aims to design an e-commerce platform that can help MSMEs in Lubuk Tarok sub-district in increasing the sales of the handicraft products they produce. In this study we used the R&D (Research and Development) approach, this R&D research is a basic research activity to obtain information on user needs (needs assessment), then continued development activities (development) to produce products and test the effectiveness of these products. This research uses the 4D development model, namely Define, Design, Develop, and Disseminate. At the Define stage, we conducted a needs analysis and identified the problems faced by WoodZone MSMEs in the Lubuk Tarok sub-district. At the Design stage, here we design an e-commerce platform architecture that suits the needs of MSMEs. At the Develop stage, we develop an e-commerce platform using OpenCart as a content management system that makes it easy to manage products, categories, and transactions. At the Desseminate stage, we conduct product testing and implementation of the e-commerce platform that has been developed and created. This research results in showing that with this e-commerce platform that has been designed using OpenCart, WoodZone MSMEs in Lubuk Tarok sub-district can more easily market the handicraft products they produce to a wider range of consumers. The features provided in this platform, such as the online payment system, inventory management, and sales analysis, which make it easy for WoodZone MSME players to run their businesses. In addition, this platform is also equipped with promotion and marketing features that can increase product visibility in the online market. The impact of this research aims to provide solutions to marketing problems carried out by MSMEs that are just starting to enter the world of digital media in the process of marketing products to consumers in a wider range.